Harnessing Generative AI to Support EFL Academic Writing: A Systematic Review of English Education Students - Desti Angraini (CV Media Inti Teknologi, 2025)
Background of Study: Generative Artificial Intelligence (AI) has increasingly influenced higher education, offering innovative possibilities for English language teaching, particularly in academic writing. While its adoption is expanding, systematic evidence on its roles, benefits, and limitations for English education students remains limited. Aims and Scope of Paper: This paper aims to systematically review empirical studies on the integration of generative AI into English education at the tertiary level. The focus is on identifying its pedagogical applications, impacts on learning, and challenges in the context of academic writing development. Methods: Following the PRISMA 2020 guidelines, relevant peer-reviewed studies published between 2020 and 2025 were collected from major academic databases. Inclusion criteria targeted studies involving English education students in higher education settings that implemented generative AI tools as part of teaching and learning activities. Results: The review highlights key benefits of generative AI, including enhanced learner autonomy, improved writing quality through AI-assisted feedback, and increased engagement. However, challenges were identified, such as ethical concerns, the risk of over-reliance, and the need to develop students’ critical literacy skills in using AI-generated content. Conclusion: Integrating generative AI into English education has the potential to significantly improve academic writing skills and student engagement. Nevertheless, effective implementation requires clear pedagogical frameworks, ethical guidelines, and targeted training to ensure responsible and balanced use. The findings provide practical insights for educators, curriculum designers, and policymakers in optimizing AI integration into English language teaching and learning.